2022
DOI: 10.3390/ncrna8060075
|View full text |Cite
|
Sign up to set email alerts
|

Exosome RNA Sequencing as a Tool in the Search for Cancer Biomarkers

Abstract: Numerous noninvasive methods are currently being used to determine biomarkers for diseases such as cancer. However, these methods are not always precise and reliable. Thus, there is an unmet need for better diagnostic and prognostic biomarkers that will be used to diagnose cancer in early, more treatable stages of the disease. Exosomes are extracellular vesicles of endocytic origin released by the majority of cells. Exosomes contain and transport nucleic acids, proteins, growth factors, and cytokines from thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 104 publications
(150 reference statements)
0
3
0
Order By: Relevance
“…Studies of the functional heterogenicity of EXOs have shown that even small variations in their content can result in a range of recipient cell outcomes, from enhanced survival and immunomodulation to apoptosis [29]. Advancements in next-generation sequencing have improved our understanding of exosomal cargo and thus their therapeutic use [30]. Here, we have demonstrated that closely mimicking the plasma membrane epitopes of host cells by using LAMA2-EXOs facilitates targeted delivery and enhanced EXO uptake by cardiomyocytes, leading to a noticeable protective effect against ischemia-reoxygenation injury.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the functional heterogenicity of EXOs have shown that even small variations in their content can result in a range of recipient cell outcomes, from enhanced survival and immunomodulation to apoptosis [29]. Advancements in next-generation sequencing have improved our understanding of exosomal cargo and thus their therapeutic use [30]. Here, we have demonstrated that closely mimicking the plasma membrane epitopes of host cells by using LAMA2-EXOs facilitates targeted delivery and enhanced EXO uptake by cardiomyocytes, leading to a noticeable protective effect against ischemia-reoxygenation injury.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in human medicine have tried to identify novel diagnostic and prognostic biomarkers for the management of cancer patients 11, (38)(39)(40)(41). New kinds of biomarkers with performant sensitivity and specificity are required to assess the same in veterinary medicine, especially for high-incidence cancer diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes contain proteins, non-coding RNAs, DNA fragments, and lipids. Based on the fact that they show differential expression between normal and cancer cells, exosomal proteins can serve as prognostic and/or diagnostic markers of various diseases [ 56 ]. Exosomal proteins include: (1) membrane transport and fusion proteins, including annexin, RAB GTPases, and heat shock proteins (Hsp60, Hsp70, and Hsp90); (2) tetraspanins, including CD9, CD63, CD81, CD82, CD106, and intercellular adhesion molecule (ICAM); (3) MVB-related proteins, including ALIX and TSG101; and (4) cytoskeletal proteins, such as actin and myosin.…”
Section: Contents Of Exosomes: Exosomal Proteinsmentioning
confidence: 99%